Playwrights for Tomorrow : A Collection of Plays, Volume 1 - Ballet, Arthur H. (Book collections on Project MUSE., 2014)
Playwrights for Tomorrow was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Four young playwrights, James Schevill, Megan Terry, Elizabeth Johnson, and Terrence McNally, are represented in this collection, which includes four one-act plays and one three-act play. The authors are writers who have participated in an experimental program at the University of Minnesota under the auspices of the Office for Advanced Drama Research, of which Arthur H. Ballet is the director. The program of the Office for Advanced Drama Research, established with the aid of a grant from the Rockefeller Foundation, provides an opportunity for promising young playwrights to develop their talents in a situation which offers them, among other advantages, the chance to have their plays actually produced. Dr. Ballet describes the project in an introduction. The plays which make up this collection are two related one-act plays, The Space Fan and The Master (titled together American Power), by James Schevill; Ex-Miss Cooper Queen on a Set of Pills by Megan Terry; A Bad Play for an Old Lady by Elizabeth Johnson; and And Things That Go Bump in the Night by Terrence McNally. Each playwright provides a discussion of his work, and production data are given. All except one of the plays were produced at the Tyrone Guthrie Theatre in Minneapolis. In addition, one of them, And Things That Go Bump in the Night, has been given on Broadway. Just as the experimental productions helped the playwrights evaluate their work, publication of the plays will, it is hoped, contribute further to the critical process by giving the plays the benefits of wider audiences and broader appraisal. Another collection of plays by writers associated with the program of the Office for Advanced Drama Research is available in a second volume.